Short-Circuit Performance Investigation of 10kV+ Rated SiC n-IGBT - Almpanis, Ioannis; Evans, Paul; Antoniou, Marina; Gammon, Peter; Empringham, Lee; Udrea, Florin; Mawby, Philip; Lophitis, Neophytos (My University, 2022)
This paper presents a comprehensive short-circuit robustness investigation of 4H- Silicon Carbide (SiC) n-type Insulated Gate Bipolar Transistors (nIGBTs) for Medium-Voltage and High- Voltage applications. Numerical electrothermal TCAD simulations evaluate the IGBT short-circuit behaviour under various conditions and device parameters variation. The internal device current density and temperature distribution show that the parasitic thyristor latch-up and the thermally-assisted leakage current generation can be the failure mechanism of SiC nIGBT when the device temperature in the p-well/n-emitter interface region is about 1500K.
Keywords: electrothermal simulation; parasitic thyristor latch-up; short-circuit capability; SiC IGBT